Pengaruh Kepemimpinan, Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. BPR Pusaka Dana - Pebriansyah Pebriansyah; Riki Haryono (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Funding institutions are currently developing very rapidly, in order to survive, the company must be able to compete and create employees who can contribute and reach predetermined targets. The purpose of this study was to determine the effect of Leadership, Motivation and Work Discipline on Employee Performance at PT. BPR Pusaka Dana. The method used in this research is quantitative descriptive analysis. The performance statistical test to measure how much influence between the variables studied and other statistical calculation process using SPSS version 21.0 program. While the population in this study is Employee at BPR Pusaka Dana which amounted to 81 people and all members of the population sampled for the determination of respondents. The result of this research indicate that there is a partial influence between leadership on Employee Performance amound t-count 11.690 at the significance level of 0.000. There is partial influence between Motivation to the Employee Performance of t-count 10.555 at a significance level of 0.000. There is partial influence between Work Discipline on Employee Performance amound t-count 12.910 at a significance level of 0.000. And the simultaneous relationship occurs between the leadership, Motivation and Work Discipline to the positive competence of F-count 73.657 at the significance level of 0.000. Conclusion from research result that is a positive and significant influence between leadership, Motivation and Work Discipline on Employee performance either partially or simultaneously.